An organic electroluminescent compound and its preparation method and luminescent display panel
By developing an aromatic amine-based organic electroluminescent compound with a high refractive index, the problems of the reduction of color purity and light extraction efficiency of blue light emitting elements in the prior art are solved, and high efficiency and long-life organic EL elements are realized.
Patent Information
- Application Number
- CN202111388708.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-11-22
AI Technical Summary
In the case of blue luminescence, the conventional organic electroluminescent elements have problems such as reducing color purity and decreasing light extraction efficiency, and the refractive index of the existing CPL materials is not sufficient to meet the requirements of high refractive index.
An aromatic amine-based organic electroluminescent compound has been developed, which has a structural design that is capable of being absorbed in the respective wavelength regions of blue, green and red, and has high refractive index, film stability and durability, and is used as a cap layer material.
By using the high refractive index organic electroluminescent compound as the cap layer material, the light extraction efficiency and luminous efficiency of the organic EL element are significantly improved, and high efficiency and long-life organic EL element are achieved.
Smart Images

Figure CN116143735B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic electroluminescent materials, and more particularly to an organic electroluminescent compound and a preparation method thereof and a light-emitting display panel. Background Art
[0002] Organic Light Emitting Display (OLED) is a new type of flat panel display. After decades of development, it has made great progress. In the two important fields of lighting and display, OLED occupies an important share, especially in the field of flat panel display. The saying "big screen or small screen is available to everyone" has become a reality.
[0003] Until now, there have been many improvements for the practical application of organic EL elements, and the various functions have been further subdivided. On the substrate, an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a cathode are arranged in order according to their functions. In organic electroluminescent devices, high efficiency and durability can be achieved by a light-emitting element with a bottom-emitting structure that emits light from the bottom.
[0004] In such a light-emitting element, when the light emitted from the light-emitting layer is incident on other films, if it is incident at an angle above a certain angle, it will be totally reflected at the interface between the light-emitting layer and the other films. Therefore, only a part of the emitted light can be used. In recent years, in order to improve the light extraction efficiency, some people have proposed to set a high refractive index cap layer on the outside of the semi-transparent electrode with a low refractive index to adjust the optical interference distance, suppress the reflection of external light, and suppress the extinction caused by the movement of surface plasma energy, thereby improving the light extraction efficiency and improving the luminous efficiency.
[0005] As a capping layer for adjusting the refractive index, aluminum quinoline (hereinafter referred to as Alq3) is known to be used. Alq3 is often used as a green light-emitting material or electron transport material, but it has weak absorption near 450nm used by blue light-emitting elements. Therefore, in the case of blue light-emitting elements, there will be a problem of reduced color purity and reduced light extraction efficiency.
[0006] Existing CPL materials have improved the light extraction efficiency to a certain extent. However, the refractive index of existing CPL materials is generally below 1.9, which cannot meet the requirements of high refractive index, and the luminous efficiency is low. In order to improve the characteristics of organic EL elements, especially to significantly improve the light extraction efficiency, it is necessary to develop a material with a high refractive index to improve the light extraction efficiency and solve the problem of luminous efficiency. As for the cap layer material, it is necessary to seek a material with a high refractive index and excellent film stability or durability. Summary of the invention
[0007] In view of this, the object of the present invention is to provide an aromatic amine organic electroluminescent compound, a preparation method thereof and a light-emitting display panel. The capping layer composed of a material having no absorption in the respective wavelength regions of blue, green and red has a high refractive index, film stability and excellent durability, and can greatly improve the light extraction efficiency and luminous efficiency of the organic EL element.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] An organic electroluminescent compound, the general structural formula of which is shown in Chemical Formula 1:
[0010]
[0011] wherein X and Z are each independently selected from O or S;
[0012] Y1, Y2, Y3, and Y4 are the same or different, and Y1-Y4 are each independently selected from O, S, CR1R2, SiR3R4, or NR5;
[0013] L1, L2, L3 are the same or different and L1-L3 are independently selected from substituted or unsubstituted C6-C60 aryl groups or substituted or unsubstituted 3-30-membered heteroaryl groups; at least one heteroatom thereof is O, S, N or Si;
[0014] Ar is selected from substituted or unsubstituted C6-C30 aromatic groups, and Ar can be cyclically bonded to the 1,2, 2,3, or 3,4 positions of the benzene ring;
[0015] Ar1 is selected from substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted 3-30 membered heterocycloalkyl, wherein at least one heteroatom thereof is O, S, N or Si; substituted or unsubstituted C6-C60 aryl, or substituted or unsubstituted 3-30 membered heteroaryl, wherein at least one heteroatom thereof is O, S, N or Si, and the heteroatom is preferably N atom;
[0016] R1-R5 are each independently selected from hydrogen, deuterium, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C2-C30 alkenyl, substituted or unsubstituted C2-C30 alkynyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted 3-30 membered heterocycloalkyl, wherein at least one heteroatom thereof is O, S, N or Si; substituted or unsubstituted C6-C60 aryl, substituted or unsubstituted 3-20 membered heteroaryl, wherein at least one heteroatom thereof is O, S, N or Si, and the heteroatom is preferably N atom; substituted or unsubstituted C6-C60 aryloxy, substituted or unsubstituted C1-C20 alkoxy, substituted or unsubstituted C6-C60 arylamine, substituted or unsubstituted C1-C20 alkylamine;
[0017] or,
[0018] It is connected with one or more adjacent substituents to form a monocyclic ring or a 3- to 30-membered alicyclic ring or an aromatic ring, one or more carbon atoms of which may be replaced by at least one heteroatom selected from nitrogen, oxygen or sulfur.
[0019] Preferably, Y1, Y2, Y3 and Y4 are each independently selected from CR3R4.
[0020] Preferably, L1-L3 are each independently selected from the following structures:
[0021]
[0022] Preferably, the R1-R7 are each independently selected from hydrogen, deuterium, substituted or unsubstituted C1-C30 alkyl, substituted or unsubstituted C3-C30 cycloalkyl, substituted or unsubstituted 3-30 membered heterocycloalkyl, wherein at least one hetero atom thereof is O, S, N or Si, and the hetero atom is preferably N atom; substituted or unsubstituted C6-C60 aryl, substituted or unsubstituted 3-20 membered heteroaryl, wherein at least one hetero atom thereof is O, S, N or Si, and the hetero atom is preferably N atom; substituted or unsubstituted C6-C60 aryloxy, substituted or unsubstituted C6-C60 arylamine;
[0023] or,
[0024] It is connected with one or more adjacent substituents to form a monocyclic ring or a 3- to 30-membered alicyclic ring or an aromatic ring, one or more carbon atoms of which may be replaced by at least one heteroatom selected from nitrogen, oxygen or sulfur.
[0025] Preferably, Ar1 is selected from the following structures:
[0026]
[0027] Preferably, the chemical formula 1 comprises the following general formula:
[0028]
[0029] In the present invention, the "substitution" in the so-called substitution or non-substitution means that the hydrogen atom bonded to the carbon atom of the compound is changed into another substituent, and the position of substitution is not limited as long as the position is the position where the hydrogen atom is substituted (that is, the position where the substituent can be substituted), and when two or more substituents are substituted, the two or more substituents may be the same as or different from each other.
[0030] That is, the "substituted" in the above-mentioned "substituted or unsubstituted" may preferably be one or more of deuterium, cyano, halogen, nitro, hydroxyl, phosphate, borane, silicon, C1-C10 alkyl, C2-C20 alkenyl, C2-C20 alkynyl, C6-C20 aryl, 3-membered to 10-membered heteroaryl, C1-C10 alkoxy, and C6-C20 arylamino.
[0031] Specifically, the chemical formula 1 is preferably selected from any one of the following structures:
[0032]
[0033]
[0034]
[0035] Another object of the present invention is to provide a method for preparing the above-mentioned organic electroluminescent compound, and the synthesis route is as follows:
[0036]
[0037] In the above formula, Ar, Ar1, X, Y1-Y4, Z, L1, L2, L3 are consistent with the same parts as those in the above chemical formula 1, wherein Hal1-Hal2 are each independently selected from chlorine, bromine or iodine;
[0038] The specific preparation method is as follows:
[0039] Step 1:
[0040] Under nitrogen protection, raw materials A and B are dissolved in a mixed solution of toluene, ethanol and water, tetrakistriphenylphosphine palladium and potassium carbonate are added, stirred evenly, heated and refluxed to obtain intermediate 1;
[0041] Step 2:
[0042] Under nitrogen protection, the intermediate 1 and the raw material C are dissolved in a toluene solution, tri(dibenzylideneacetone)dipalladium, tri-tert-butylphosphine and sodium tert-butoxide are added, stirred evenly, heated and refluxed to obtain chemical formula 1.
[0043] Preferably, the above step 1 specifically includes:
[0044] Under nitrogen protection, raw material A (1.0 eq) and raw material B (1.0 eq) were dissolved in a mixed solution of toluene, ethanol and water (Vtol:V:V=3:1:1), tetrakistriphenylphosphine palladium (0.01 eq) and potassium carbonate (2.0 eq) were added, stirred evenly, heated to 90°C, and refluxed for 5 hours. After the solution was cooled to room temperature, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain solid organic matter. Recrystallized in toluene, filtered, the filter cake was rinsed with petroleum ether, and dried in a 65°C oven for 12 hours to obtain intermediate 1;
[0045] The above step 2 specifically includes:
[0046] Under nitrogen protection, the intermediate 1 (1.0 eq) and the raw material C (1.0 eq) were dissolved in a toluene solution, tri(dibenzylideneacetone)dipalladium (0.01 eq), tri-tert-butylphosphine (0.05 eq) and sodium tert-butoxide (2.0 eq) were added, stirred evenly, heated to 90°C, and refluxed for 5 hours; after the reaction was completed, the temperature was slightly lowered, diatomaceous earth was used for filtration, salt and catalyst were removed, the filtrate was cooled to room temperature, washed three times with water, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, anhydrous magnesium sulfate was used for drying, and a rotary evaporator was used to remove the solvent to obtain solid organic matter. A small amount of dichloromethane was used to completely dissolve the solid organic matter, and then it was slowly added dropwise to the petroleum ether solution, stirred evenly, a precipitate was precipitated, and the solid was obtained by suction filtration, and it was successively rinsed with anhydrous ethanol and petroleum ether, and dried to prepare chemical formula 1.
[0047] Another object of the present invention is to provide an organic light-emitting display panel, which includes an organic light-emitting device, wherein the organic light-emitting device includes a capping layer, an anode, a cathode, and an organic layer located between the anode and the cathode. The organic layer includes a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, and an electron injection layer. The material of at least one of the capping layer, the hole injection layer, the hole transport layer, the light-emitting layer, the electron transport layer, and the electron injection layer is the organic light-emitting compound described in the present invention.
[0048] In the present invention, the thickness of the cap layer of the organic EL element is preferably in the range of 50 nm to 70 nm, and more preferably in the range of 55 nm to 65 nm.
[0049] In the present invention, the pre-transmission wavelength of the capping layer of the organic EL element is between 460 nm and 620 nm, and the refractive index of the capping layer is preferably greater than 2.0, and more preferably greater than 2.1.
[0050] In the organic EL element of the present invention, the cap layer can be produced by laminating two or more different constituent materials.
[0051] In the organic light-emitting display panel of the present invention, the anode material can be selected from metals such as copper, gold, silver, iron, chromium, nickel, manganese, palladium, platinum, etc. and their alloys; metal oxides such as indium oxide, zinc oxide, indium tin oxide (ITO), indium zinc oxide (IZO), etc.; conductive polymers such as polyaniline, polypyrrole, poly (3-methylthiophene), etc. In addition to the above materials that facilitate hole injection and their combinations, the anode material can also include other known materials suitable for the anode.
[0052] In the organic light-emitting display panel of the present invention, the cathode material can be selected from metals such as aluminum, magnesium, silver, indium, tin, titanium, etc. and their alloys, which can improve the quantum efficiency and stability of the device and form a stable and strong metal film on the organic film; multi-layer metal materials such as LiF / Al, LiO2 / Al, BaF2 / Al, etc. can obtain higher luminous efficiency. In addition to the above materials and combinations thereof that facilitate electron injection, the cathode material can also include other known materials suitable for the cathode.
[0053] The above-mentioned organic light-emitting display panel is prepared by the following method: forming an anode on a transparent or opaque smooth substrate, forming an organic layer on the anode, and forming a cathode on the organic layer. The formation of the organic thin layer can adopt known film-forming methods such as evaporation, sputtering, spin coating, dipping, ion plating, etc. Finally, a layer of organic optical cap layer CPL (cap layer) is prepared on the cathode. The material of the optical cap layer CPL is the aromatic amine compound described in the present invention. The optical cap layer CPL can be prepared by evaporation or solution processing. Solution processing methods include inkjet printing, spin coating, doctor blade coating, screen printing, roll-to-roll printing and other methods.
[0054] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0055] The organic EL element of the present invention uses an organic EL element material with high refractive index, good thin film stability and excellent durability as the material of the cap layer. Therefore, compared with the known organic EL elements, the light extraction efficiency is greatly improved, thereby achieving a high-efficiency, long-life organic EL element.
[0056] Since naphthobenzofuran or naphthobenzofuran compounds are introduced in the present invention, a conjugated large plane is formed with other groups while maintaining a high Tg (glass ring transition temperature), thereby achieving a high refractive index. When it is used as a capping layer of an organic light-emitting display device, the microcavity effect can be adjusted, thereby improving the light extraction efficiency of a top-emitting organic photoelectric device. Moreover, these aromatic amine compounds have a high extinction coefficient before 430nm, which is conducive to the absorption of ultraviolet light, and effectively block water and oxygen in the external environment, protecting the OLED display panel from water and oxygen erosion, and there is almost no absorption after 430nm, ensuring the light extraction efficiency, thereby realizing a high-efficiency, long-life organic EL element. BRIEF DESCRIPTION OF THE DRAWINGS
[0057] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0058] Figure 1 nk curve diagram of compound 33, comparative compound 1 and comparative compound 2 in the example of the present invention. DETAILED DESCRIPTION
[0059] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] Example 1
[0061]
[0062] Under nitrogen protection, raw material A-1 (30.00mmol) and raw material B-1 (30.00mmol) were dissolved in a mixed solution of 130.00ml toluene, ethanol and water (Vtol:V:V=3:1:1), tetrakistriphenylphosphine palladium (0.30mmol) and potassium carbonate (60.00mmol) were added, stirred evenly, heated to 90°C, and refluxed for 5 hours. After the solution was cooled to room temperature, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain solid organic matter. Recrystallized in toluene, filtered, the filter cake was rinsed with petroleum ether, and dried in a 65°C oven for 12h to obtain intermediate 1 (9.13g, yield: 81.51%).
[0063]
[0064] Under nitrogen protection, the intermediate 1 (24.11 mmol) and the raw material C-1 (24.11 mmol) were dissolved in 180.00 ml of toluene solution, tri(dibenzylideneacetone)dipalladium (0.24 mmol), tri-tert-butylphosphine (1.21 mmol) and sodium tert-butoxide (48.22 mmol) were added, stirred evenly, heated to 90°C, and refluxed for 5 hours; after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain solid organic matter. A small amount of dichloromethane was used to completely dissolve the solid organic matter, and then slowly added dropwise to the petroleum ether solution and stirred evenly. A precipitate was precipitated and the solid was filtered out. It was washed with anhydrous ethanol and petroleum ether in turn and dried to prepare compound 1 (13.12 g, yield: 78.44%, Mw: 693.80).
[0065] The obtained compound-1 was tested and analyzed, and the results were as follows:
[0066] HPLC purity: >99%.
[0067] Mass spectrometry test: theoretical value is 693.81; tested value is 693.47.
[0068] Elemental Analysis:
[0069] Calculated values: C, 86.56; H, 4.50; N, 2.02; O, 6.92.
[0070] The test values are: C, 86.19; H, 4.83; N, 2.27; O, 7.26.
[0071] Example 2
[0072]
[0073] Under nitrogen protection, raw material A-33 (30.00mmol) and raw material B-33 (30.00mmol) were dissolved in a mixed solution of 130.00ml toluene, ethanol and water (Vtol:V:V=3:1:1), tetrakistriphenylphosphine palladium (0.30mmol) and potassium carbonate (60.00mmol) were added, stirred evenly, heated to 90°C, and refluxed for 5 hours. After the solution was cooled to room temperature, the organic phase was retained, and the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain solid organic matter. Recrystallized in toluene, filtered, the filter cake was rinsed with petroleum ether, and dried in a 65°C oven for 12h to obtain intermediate 1 (9.13g, yield: 81.52%).
[0074]
[0075] Under nitrogen protection, the intermediate 3 (24.11mmol) and the raw material C-33 (24.11mmol) were dissolved in 180.00ml toluene solution, tri(dibenzylideneacetone)dipalladium (0.24mmol), tri-tert-butylphosphine (1.21mmol) and sodium tert-butoxide (48.22mmol) were added, stirred evenly, heated to 90°C, and refluxed for 5h; after the reaction was completed, the temperature was slightly lowered, and diatomaceous earth was used for filtration to remove salt and catalyst. After the filtrate was cooled to room temperature, it was washed three times with water, the organic phase was retained, and the aqueous phase was then extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain solid organic matter. A small amount of dichloromethane was used to completely dissolve the solid organic matter, and then slowly added dropwise to the petroleum ether solution and stirred evenly. A precipitate was precipitated and the solid was filtered out. It was washed with anhydrous ethanol and petroleum ether in turn and dried to prepare compound 33 (13.10 g, yield: 78.31%, Mw: 693.80).
[0076] The obtained compound-33 was tested and analyzed, and the results were as follows:
[0077] HPLC purity: >99%.
[0078] Mass spectrometry test: theoretical value is 693.80; tested value is 693.35.
[0079] Elemental Analysis:
[0080] Calculated values: C, 86.56; H, 4.50; N, 2.02; O, 6.92.
[0081] The test values are: C, 86.22; H, 4.71; N, 2.41; O, 7.25.
[0082] Example 3
[0083]
[0084] Under nitrogen protection, raw material A-52 (30.00mmol) and raw material B-52 (30.00mmol) were dissolved in a mixed solution of 180.00ml toluene, ethanol and water (Vtol:V:V=3:1:1), tetrakistriphenylphosphine palladium (0.30mmol) and potassium carbonate (60.00mmol) were added, stirred evenly, heated to 90°C, and refluxed for 5 hours. After the solution was cooled to room temperature, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain solid organic matter. Recrystallized in toluene, filtered, the filter cake was rinsed with petroleum ether, and dried in a 65°C oven for 12h to obtain intermediate 1 (10.79g, yield: 80.06%).
[0085]
[0086] Under nitrogen protection, the intermediate 3 (22.25mmol) and the raw material C-52 (22.25mmol) were dissolved in 220.00ml toluene solution, tri(dibenzylideneacetone)dipalladium (0.22mmol), tri-tert-butylphosphine (1.12mmol) and sodium tert-butoxide (44.50mmol) were added, stirred evenly, heated to 90°C, and refluxed for 5h; after the reaction was completed, the temperature was slightly lowered, diatomaceous earth was used for filtration to remove salt and catalyst, and the filtrate was cooled to room temperature and washed with water three times, the organic phase was retained, and then the aqueous phase was extracted with ethyl acetate; after the organic phases were combined, they were dried with anhydrous magnesium sulfate, and the solvent was removed with a rotary evaporator to obtain solid organic matter. A small amount of dichloromethane was used to completely dissolve the solid organic matter, and then slowly added dropwise to the petroleum ether solution and stirred evenly. A precipitate was precipitated and the solid was filtered out. It was washed with anhydrous ethanol and petroleum ether in turn and dried to prepare compound 52 (15.77 g, yield: 76.83%, Mw: 922.10).
[0087] The obtained compound-52 was tested and analyzed, and the results were as follows:
[0088] HPLC purity: >99%.
[0089] Mass spectrometry test: theoretical value is 920.10; tested value is 919.87.
[0090] Elemental Analysis:
[0091] Calculated values: C, 88.58; H, 4.70; N, 1.52; O, 5.21.
[0092] The test values are: C, 88.18; H, 4.96; N, 1.77; O, 5.56.
[0093] The synthesis methods of other compounds are the same as those in the above examples, which are not described one by one here. The mass spectra and molecular formulas of other synthesis examples are shown in Table 1 below:
[0094] Table 1:
[0095]
[0096]
[0097] Using the compound of the present invention and comparative compound 1 and comparative compound 2 (the structural formulas of comparative compound 1 and comparative compound 2 are shown below), a vapor-deposited film with a film thickness of 50 nm was prepared on a substrate, and the refractive index at 450 nm, 530 nm, and 635 nm was measured using a spectrophotometer. The measurement results are summarized in Table 2, as well as the nk coefficient curve, as shown in Table 2. Figure 1 shown.
[0098]
[0099] Table 2: Thermal properties and refractive index test results
[0100]
[0101] It can be seen from Table 2 that the refractive index of the compounds prepared by the present invention at wavelengths of 450nm, 530nm and 635nm is above 2.0, which meets the refractive index requirements of the light-emitting device for CPL. The extinction coefficient k value is almost 0 after the blue light wavelength of 430nm, which will not affect the luminescence of the luminescent layer material in the blue light region. Therefore, it can bring higher luminous efficiency. In addition, it can be found in Table 2 that the glass transition temperature of the compounds is higher than 130°C, which means that in the compounds of the present invention, the film state is stable. Figure 1 It can be more intuitively seen that the n value of the compound 33 of the present invention is higher than that of the comparative compound, which indicates that the luminescence efficiency of the compound of the present invention is higher than that of the comparative compound 1 and the comparative compound 2.
[0102] Device Example 1 (Red Light Device)
[0103] The following examples provide applications of the aromatic amine compounds of the present invention in organic light-emitting devices, and illustrate the technical effects achieved by the aromatic amine compounds of the present invention in practical applications.
[0104] The structure of the prepared OLED device is: ITO anode / HIL / HTL / EML / ETL / EIL / cathode / light extraction layer
[0105] a. ITO anode: the coating thickness is The ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate was cleaned twice in distilled water, ultrasonically cleaned for 30 minutes, and then repeatedly cleaned twice with distilled water, ultrasonically cleaned for 10 minutes. After washing, it was ultrasonically cleaned with methanol, acetone, and isopropanol in sequence (5 minutes each time), dried, and then transferred to a plasma cleaning machine for washing for 5 minutes. It was then sent to a vapor deposition machine, and the substrate was used as the anode, and other functional layers were deposited thereon in sequence.
[0106] b. HIL (hole injection layer): The hole injection layer materials HT-1 and P-dopant are vacuum evaporated at a deposition rate of 97:3, and the thickness is 10 nm;
[0107] c. HTL (hole transport layer): At a deposition rate of 100%, 130 nm of HT-1 was vacuum-deposited on the hole injection layer as a hole transport layer.
[0108] d. Light-emitting auxiliary layer: At a deposition rate of , 95nm EB-1 was vacuum-deposited on the hole injection layer as a light-emitting auxiliary layer;
[0109] e. EML (light-emitting layer): Then on the above-mentioned light-emitting auxiliary layer, The host material (Host) and the dopant material (Dopant) with a thickness of 40nm are vacuum-deposited as the light-emitting layer at a deposition rate of 100 nm. The chemical formulas of the Host and Dopant are as follows. The deposition rate ratio of the Host and Dopant is 97:3.
[0110] f. HB (hole blocking layer): At a deposition rate of , HB with a thickness of 5.0 nm was vacuum deposited as a hole blocking layer.
[0111] g. ETL (Electron Transport Layer): The evaporation rate of ET-1 and Liq was vacuum evaporated to a thickness of 35 nm as the electron transport layer, and the chemical formula of ET-1 is shown below. The evaporation rate ratio of ET-1 and Liq was 50:50.
[0112] h. EIL (electron injection layer): At a evaporation rate of , a 1.0 nm Yb film layer was evaporated to form an electron injection layer.
[0113] i. Cathode: The evaporation rate ratio is 1:9, and magnesium and silver are evaporated at 18nm, and the evaporation rate ratio is 1:9 to obtain an OLED device.
[0114] j. Light extraction layer: The compound 1 provided in the above embodiment was vacuum evaporated on the cathode with a thickness of 70 nm at a deposition rate as a light extraction layer.
[0115] k. Then the vapor-deposited substrate is packaged. First, the cleaned cover is coated with UV glue using glue coating equipment, and then the coated cover is moved to the pressing section, the vapor-deposited substrate is placed on the upper end of the cover, and finally the substrate and cover are bonded by bonding equipment, and the UV glue is cured by light.
[0116] The chemical structural formulas of the corresponding compounds used in the above devices are shown below:
[0117]
[0118] Device Examples 2 to 8
[0119] According to the method of device example 1, the cathode cap layer material was replaced with compounds 20, 31, 33, 41, 52, 64, and 84, respectively, to prepare organic electroluminescent devices, which were respectively recorded as device examples 2 to 8.
[0120] Device Comparative Example 1
[0121] An organic electroluminescent device comparative example 1 was prepared according to the method of device example 1. The difference was that the CPL layer material compound was replaced with comparative compound 1, and other materials such as the light-emitting layer material were the same. Among them, the structural formula of comparative compound 1 is as follows:
[0122] Device Comparison Example 2
[0123] An organic electroluminescent device comparative example 1 was prepared according to the method of device example 1. The difference was that the CPL layer material compound was replaced with comparative compound 2, and other materials such as the light-emitting layer material were the same. Among them, the structural formula of comparative compound 2 is as follows:
[0124] Device Comparison Example 3
[0125] An organic electroluminescent device comparative example 3 was prepared according to the method of device example 1. The difference is that the CPL layer material compound is replaced by comparative compound 3, and other materials such as the light-emitting layer material are the same. Among them, the structural formula of comparative compound 3 is as follows:
[0126] Device Comparison Example 4
[0127] An organic electroluminescent device comparative example 4 was prepared according to the method of device example 1. The difference was that the CPL layer material compound was replaced with comparative compound 4, and other materials such as the light-emitting layer material were the same. Among them, the structural formula of comparative compound 4 is as follows:
[0128]
[0129] The driving voltage, luminous efficiency and life of the organic electroluminescent devices obtained from the above device embodiments 1 to 8 and device comparative examples 1 to 4 were characterized at a brightness of 6000 (nits). The test results are shown in Table 3 below:
[0130] Table 3:
[0131]
[0132]
[0133] Device Example 9 (Green Light Device)
[0134] The following examples provide applications of the aromatic amine compounds of the present invention in organic light-emitting devices, and illustrate the technical effects achieved by the aromatic amine compounds of the present invention in practical applications.
[0135] The structure of the prepared OLED device is: ITO anode / HIL / HTL / EML / ETL / EIL / cathode / light extraction layer
[0136] a. ITO anode: the coating thickness is The ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate was cleaned twice in distilled water, ultrasonically cleaned for 30 minutes, and then repeatedly cleaned twice with distilled water, ultrasonically cleaned for 10 minutes. After washing, it was ultrasonically cleaned with methanol, acetone, and isopropanol in sequence (5 minutes each time), dried, and then transferred to a plasma cleaning machine for washing for 5 minutes. It was then sent to a vapor deposition machine, and the substrate was used as the anode, and other functional layers were deposited thereon in sequence.
[0137] b. HIL (hole injection layer): The hole injection layer materials HT-1 and P-dopant are vacuum evaporated at a deposition rate of 97:3, and the thickness is 10 nm;
[0138] c. HTL (hole transport layer): At a deposition rate of 100%, 130 nm of HT-1 was vacuum-deposited on the hole injection layer as a hole transport layer.
[0139] d. Light-emitting auxiliary layer: At a deposition rate of 100%, 45nm EB-2 was vacuum-deposited on the hole transport layer as a light-emitting auxiliary layer;
[0140] e. EML (light-emitting layer): Then on the above-mentioned light-emitting auxiliary layer, The main material (Host-1 and Host-2) and the dopant material (Dopant) are vacuum-deposited at a deposition rate of 40 nm as the light-emitting layer. The chemical formulas of Host-1, Host-2 and Dopant are shown below. The deposition rate ratio of the main material (Host-1 and Host-2) to the dopant material (Dopant) is 94:6, and the deposition rate ratio of Host-1 to Host-2 is 4:6.
[0141] f. HB (hole blocking layer): At a deposition rate of , HB with a thickness of 5.0 nm was vacuum deposited as a hole blocking layer.
[0142] g. ETL (Electron Transport Layer): The evaporation rate of ET-1 and Liq was vacuum evaporated to a thickness of 35 nm as the electron transport layer, and the chemical formula of ET-1 is shown below. The evaporation rate ratio of ET-1 and Liq was 50:50.
[0143] h. EIL (electron injection layer): At a evaporation rate of , a 1.0 nm Yb film layer was evaporated to form an electron injection layer.
[0144] i. Cathode: The evaporation rate ratio is 1:9, and magnesium and silver are evaporated at 18nm, and the evaporation rate ratio is 1:9 to obtain an OLED device.
[0145] j. Light extraction layer: The compound 1 provided in the above embodiment was vacuum evaporated on the cathode with a thickness of 70 nm at a deposition rate as a light extraction layer.
[0146] k. Then the vapor-deposited substrate is packaged. First, the cleaned cover is coated with UV glue using glue coating equipment, and then the coated cover is moved to the pressing section, the vapor-deposited substrate is placed on the upper end of the cover, and finally the substrate and cover are bonded by bonding equipment, and the UV glue is cured by light.
[0147] The chemical structural formulas of the corresponding compounds used in the above devices are shown below:
[0148]
[0149] Device Examples 10 to 16
[0150] According to the method of device example 1, the cathode cap layer material was replaced with compounds 20, 31, 33, 41, 52, 64, and 84, respectively, to prepare organic electroluminescent devices, which were respectively recorded as device examples 10 to 16.
[0151] Device Comparison Example 5
[0152] An organic electroluminescent device comparative example 5 was prepared according to the method of device example 9. The difference is that the CPL layer material compound is replaced by comparative compound 1, and other materials such as the light-emitting layer material are the same. Among them, the structural formula of comparative compound 1 is as follows:
[0153] Device Comparative Example 6
[0154] An organic electroluminescent device comparative example 6 was prepared according to the method of device example 9. The difference was that the CPL layer material compound was replaced with comparative compound 2, and other materials such as the light-emitting layer material were the same. Among them, the structural formula of comparative compound 2 is as follows:
[0155] Device Comparison Example 7
[0156] An organic electroluminescent device comparative example 7 was prepared according to the method of device example 9. The difference is that the CPL layer material compound is replaced by comparative compound 3, and other materials such as the light-emitting layer material are the same. Among them, the structural formula of comparative compound 3 is as follows:
[0157] Device Comparison Example 8
[0158] An organic electroluminescent device comparative example 8 was prepared according to the method of device example 9. The difference is that the CPL layer material compound is replaced by comparative compound 4, and other materials such as the light-emitting layer material are the same. Among them, the structural formula of comparative compound 4 is as follows:
[0159]
[0160] The driving voltage, luminous efficiency and life of the organic electroluminescent devices obtained from the above device embodiments 9 to 16 and device comparative examples 5 to 8 were characterized at a brightness of 15000 (nits). The test results are shown in Table 3 below:
[0161] Table 4:
[0162]
[0163]
[0164] Device Example 17 (Blue Light Device)
[0165] The following examples provide applications of the aromatic amine compounds of the present invention in organic light-emitting devices, and illustrate the technical effects achieved by the aromatic amine compounds of the present invention in practical applications.
[0166] The structure of the prepared OLED device is: ITO anode / HIL / HTL / EML / ETL / EIL / cathode / light extraction layer
[0167] a. ITO anode: the coating thickness is The ITO (indium tin oxide)-Ag-ITO (indium tin oxide) glass substrate was cleaned twice in distilled water, ultrasonically cleaned for 30 minutes, and then repeatedly cleaned twice with distilled water, ultrasonically cleaned for 10 minutes. After washing, it was ultrasonically cleaned with methanol, acetone, and isopropanol in sequence (5 minutes each time), dried, and then transferred to a plasma cleaning machine for washing for 5 minutes. It was then sent to a vapor deposition machine, and the substrate was used as the anode, and other functional layers were deposited thereon in sequence.
[0168] b. HIL (hole injection layer): The hole injection layer materials HT-1 and P-dopant are vacuum evaporated at a deposition rate of 97:3, and the thickness is 10 nm;
[0169] c. HTL (hole transport layer): At a deposition rate of 100%, 130 nm of HT-1 was vacuum-deposited on the hole injection layer as a hole transport layer.
[0170] d. Light-emitting auxiliary layer: At a deposition rate of 50%, 5 nm of EB-3 was vacuum-deposited on the hole transport layer as a light-emitting auxiliary layer;
[0171] e. EML (light-emitting layer): Then on the above-mentioned light-emitting auxiliary layer, The host material (Host) and the dopant material (Dopant) are vacuum-deposited at a deposition rate of 20 nm as the light-emitting layer. The chemical formulas of the Host and Dopant are as follows. The deposition rate ratio of the Host and Dopant is 98:2.
[0172] f. HB (hole blocking layer): At a deposition rate of , HB with a thickness of 5.0 nm was vacuum deposited as a hole blocking layer.
[0173] g. ETL (Electron Transport Layer): The evaporation rate of ET-1 and Liq was vacuum evaporated to a thickness of 35 nm as the electron transport layer, and the chemical formula of ET-1 is shown below. The evaporation rate ratio of ET-1 and Liq was 50:50.
[0174] h. EIL (electron injection layer): At a evaporation rate of , a 1.0 nm Yb film layer was evaporated to form an electron injection layer.
[0175] i. Cathode: The evaporation rate ratio is 1:9, and magnesium and silver are evaporated at 18nm, and the evaporation rate ratio is 1:9 to obtain an OLED device.
[0176] j. Light extraction layer: The compound 1 provided in the above embodiment was vacuum evaporated on the cathode with a thickness of 70 nm at a deposition rate as a light extraction layer.
[0177] k. Then the vapor-deposited substrate is packaged. First, the cleaned cover is coated with UV glue using glue coating equipment, and then the coated cover is moved to the pressing section, the vapor-deposited substrate is placed on the upper end of the cover, and finally the substrate and cover are bonded by bonding equipment, and the UV glue is cured by light.
[0178] The chemical structural formulas of the corresponding compounds used in the above devices are shown below:
[0179]
[0180] Device Examples 18 to 24
[0181] According to the method of device example 1, the cathode cap layer material was replaced with compounds 20, 31, 33, 41, 52, 64, and 84, respectively, to prepare organic electroluminescent devices, which were respectively recorded as device examples 18 to 24.
[0182] Device Comparative Example 9
[0183] An organic electroluminescent device comparative example 9 was prepared according to the method of device example 17. The difference was that the CPL layer material compound was replaced with comparative compound 1, and other materials such as the light-emitting layer material were the same. Among them, the structural formula of comparative compound 1 is as follows:
[0184] Device Comparative Example 10
[0185] An organic electroluminescent device comparative example 10 was prepared according to the method of device example 17. The difference was that the CPL layer material compound was replaced with comparative compound 2, and other materials such as the light-emitting layer material were the same. Among them, the structural formula of comparative compound 2 is as follows:
[0186] Device Comparative Example 11
[0187] An organic electroluminescent device comparative example 11 was prepared according to the method of device example 17. The difference was that the CPL layer material compound was replaced with comparative compound 3, and other materials such as the light-emitting layer material were the same. Among them, the structural formula of comparative compound 3 is as follows:
[0188] Device Comparison Example 12
[0189] An organic electroluminescent device comparative example 12 was prepared according to the method of device example 17. The difference was that the CPL layer material compound was replaced with comparative compound 4, and other materials such as the light-emitting layer material were the same. Among them, the structural formula of comparative compound 4 is as follows:
[0190]
[0191] The driving voltage, luminous efficiency and life of the organic electroluminescent devices obtained from the device embodiments 17 to 24 and the device comparative examples 9 to 12 were characterized at a brightness of 1000 (nits). The test results are shown in Table 3 below:
[0192] Table 5:
[0193]
[0194]
[0195] As can be seen from Tables 3 to 5 above, the compounds of the present invention are used to prepare red light devices, green light devices, and blue light devices, respectively. Compared with device comparison examples 1 to device comparison examples 6, the devices using the compounds of the present invention as CPL materials have significantly improved luminous efficiency. This means that by including a compound with a high refractive index in the cap layer, the light extraction efficiency can be greatly improved. The compounds of the present invention are very excellent compounds for organic EL elements because of their high absorption coefficient and high refractive index, which can greatly improve the light extraction efficiency and stable film state. The organic EL element prepared by the compound can improve the luminous efficiency of the device and is an ideal CPL material.
[0196] In this specification, each embodiment is described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the embodiments can be referred to each other. For the device disclosed in the embodiment, since it corresponds to the method disclosed in the embodiment, the description is relatively simple, and the relevant parts can be referred to the method part.
[0197] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An organic electroluminescent compound, characterized in that: Its general structural formula is shown in Chemical Formula 1: wherein X and Z are each independently selected from O or S; Y1-Y4 are each independently selected from CR1R2; Ar is selected from substituted or unsubstituted C6 aryl groups, and Ar can be cyclically bonded to the 1,2, 2,3, or 3,4 positions of the benzene ring; R1-R2 are each independently selected from hydrogen; L1-L3 are each independently selected from the following structures: Ar1 is selected from the following structures:
2. An organic electroluminescent compound according to claim 1, characterized in that: The chemical formula 1 includes the following general formula:
3. An organic electroluminescent compound according to claim 1 or 2, characterized in that: Its structure is selected from any one of the following compounds:
4. A method for preparing an organic electroluminescent compound as claimed in claim 3, characterized in that: The synthesis path is as follows: In the above formula, Ar, Ar1, X, Y1-Y4, Z, L1, L2, L3 are consistent with the same parts as those in the chemical formula 1 of claim 3, wherein Hal1-Hal2 are each independently selected from chlorine, bromine or iodine; The specific preparation method is as follows: Step 1: Under nitrogen protection, raw materials A and B are dissolved in a mixed solution of toluene, ethanol and water, tetrakistriphenylphosphine palladium and potassium carbonate are added, stirred evenly, heated and refluxed to obtain intermediate 1; Step 2: Under nitrogen protection, the intermediate 1 and the raw material C are dissolved in a toluene solution, tri(dibenzylideneacetone)dipalladium, tri-tert-butylphosphine and sodium tert-butoxide are added, stirred evenly, heated and refluxed to obtain chemical formula 1.
5. The method for preparing an organic electroluminescent compound according to claim 4, characterized in that: In step 1, the molar ratio of raw material A, raw material B, tetrakistriphenylphosphine palladium and potassium carbonate is 1:1:0.01:2; the volume ratio of toluene, ethanol and water is 3:1:1; the heating temperature is 90° C. and the reflux time is 5 h.
6. The method for preparing an organic electroluminescent compound according to claim 4, characterized in that: The molar ratio of the intermediate 1, the raw material C, tri(dibenzylideneacetone)dipalladium, tri-tert-butylphosphine and sodium tert-butoxide in step 2 is 1:1:0.01:0.05:2; the heating temperature is 90° C. and the reflux time is 5 h.
7. An organic light emitting display panel, comprising an organic light emitting device, characterized in that: The organic light-emitting device comprises a capping layer, an anode, a cathode, and an organic layer located between the anode and the cathode, wherein at least one of the organic layer and the capping layer comprises the organic electroluminescent compound according to claim 3.
8. A light-emitting display panel according to claim 7, characterized in that: The organic layer comprises a hole injection layer, a hole transport layer, a light emitting layer, an electron transport layer and an electron injection layer, and at least one of the hole injection layer, the hole transport layer, the light emitting layer, the electron transport layer and the electron injection layer comprises the organic electroluminescent compound according to claim 3.
Citation Information
Patent Citations
Novel organic compound for capping layer, and organic light-emitting element comprising same
CN112745264A